The distribution of optimism across sociodemographic groups in 22 countries - Ying Chen; Laura D. Kubzansky; Eric S. Kim; Hayami Koga; Koichiro Shiba; R. Noah Padgett; Renae Wilkinson; Byron R. Johnson; Tyler J. VanderWeele (Scientific Reports)
Abstract Prior research (mainly from Western industrialized countries) documents associations between greater dispositional optimism (a generalized expectation that good things will happen) and improved health and well-being. However, less is known about whether and how levels of optimism differ across countries and across sociodemographic groups within different countries. This study presents a cross-national exploration of optimism, and its variations across sociodemographic groups. Using a sample of 202,898 adults from 22 diverse countries, we examined the relationships between optimism and key sociodemographic factors in each country separately, and cross-nationally by pooling results across countries using meta-analytic techniques. Our results suggest that mean optimism levels vary substantially across countries. Optimism also varies significantly across most of the sociodemographic factors included in our analyses. In the pooled results across countries, individuals who are older, female, married, employed, highly educated, attending religious services frequently, and native-born reported higher mean optimism levels. In the country-specific analyses, the sociodemographic variation in optimism differs across countries, indicating diverse societal influences. The findings of this study provide novel insights into the population distribution of optimism and disparities in optimism by sociodemographic groups across countries. This study provides a valuable foundation for future investigations into sociocultural influences that shape optimism.